Introduction to Thermal Cloaking Theory and Analysis in Conduction and Convection - Yeung, Woon-Shing.; Yang, Ruey-Jen.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book introduces the fundamental concepts of thermal cloaking based on transformation theory and bilayer theory, under the conduction and convection heat transfer modes. It focuses on thermal cloaking with detailed explanations of the underlying theoretical bases leading to the primary thermal cloaking results in open literature, from an engineering perspective, and with practical application in mind. Also, the authors strive to present the materials with an emphasis on the related physical phenomena and interpretation, to the extent possible. Through this book, engineering students can grasp the fundamental ideas of thermal cloaking and the associated mathematics, thus being better able to initiate their own research and explore new ideas in thermal cloaking. While not intended to be a general reference in the vast field of thermal cloaking research, this book is a unique monograph addressing the theoretical and analytical aspects of thermal cloaking within the scope mentioned above. This book also contains many independent analytical solutions to thermal cloaking problems that are not available in open literature. It is suitable for a three-credit graduate or advanced undergraduate course in engineering science. .
Introduction -- Review of Curvilinear Coordinates -- Review of Heat Conduction.-Transformation Theory for Conduction Thermal Cloaking -- Bilayer Theory for Conduction Thermal Cloaking -- General Consideration of Bilayer Thermal Cloak -- Transformation Theory for Convection Thermal Cloaking -- Bilayer Theory for Convection Thermal Cloaking -- Transient Thermal Cloaking -- Numerical Simulation and Experiments -- Prologue: Engineering Application and Perspectives.
Keywords: Mechanical engineering; Production engineering; Energy storage; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mechanical Engineering; Thermal Process Engineering; Mechanical and Thermal Energy Storage; Engineering Thermodynamics, Heat and Mass Transfer; Heat -- Transmission; Thermal barrier coatings